Evaluation and Behavior of Spanish Bodybuilders: Doping and Sports Supplements - Antonio Jesús Sánchez-Oliver; Moisés Grimaldi-Puyana; Raúl Domínguez (Biomolecules, 2019)
The use of doping agents has these days become a public health problem, as it also affects young and non-competitive amateurs in different sports. To prepare for competition, bodybuilders perform aggressive dietary protocols, so, bodybuilders frequently consume nutritional supplements (NS) and banned substances in large dosages. Thus, the aim of this study is to analyze the prevalence of banned substances consumption and NS intake in competitive level bodybuilders. A total of 48 bodybuilders (44 males and 4 females) completed a validated online questionnaire on NS consumption. The quantitative data was presented as a mean (M) ± standard deviation (SD), as well as having minimum and maximum values. The categorical variables were expressed using frequencies and percentages. 83.3% of the participants declared that they had consumed or would consume banned substances, the most consumed being anabolic steroids (72.9%). One hundred percent of those sampled use NS. Whey protein (96%), branched-chain amino acids (BCAA) (94%), creatine (85%) and vitamin complexes (83%) were the most consumed, however, there is a low consumption of certain NS which could also increase athletic performance.